Quality Of The Produced Pancong Cakes From Brown Rice Flour Substitution - Yulianti, Siska; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This research was carried out at the culinary arts workshop majoring in family welfare science in August 2021. This type of research was experimental using a completely randomized design consisting of 3 treatments and 3 repetitions. Data analysis was obtained from an organoleptic test involving 5 expert panelists. The data obtained were then analyzed using the ANOVA method, if there was a significant effect, it would be continued with the Duncan test. The results showed that the substitution of brown rice flour affected the reddish color, brown color, and texture. Which does not affect the shape, aroma, and taste. Based on the results of the study, the best shape quality (neat) cake pancong with X1 treatment with a score of 3.87, best color quality (reddish) cake pancong with X3 treatment with a score of 3.27, best color quality (brown) cake pancong with X3 treatment with a score of 3.27, the best quality of aroma (smelling red rice) with treatment X3 with a score of 1.27, pancong cake with the best quality of texture (soft) with treatment X3 with a score of 3.40, pancong cake with the best taste (sweet) quality with X3 treatment with a score of 3.40, so it is very suitable for consumption. So for further research, it is recommended that the use of brown rice flour should be as much as 45%, namely with treatment (X3) but the best texture quality is found in treatment (X1) with a value of 3.20.